Broadcast spawning pattern of Acropora cytherea and Acropora clathrata from Inshore Reef Area in Kuantan Coastal Region - Mohd Hanapiah, Muhammad Faiz; Saad, Shahbudin; Ahmad, Zuhairi (2020)
Acropora sp. is the second-most abundant among the coral genera in the Kuantan coastal region (KCR) located on the east coast of Peninsular Malaysia. This study investigated the timing of coral spawning of two Acropora species; Acropora cytherea and Acropora clathrata through dissection and histological analyses of coral fragments that were collected during predicted spawning months (March until May 2018) from Balok reef, Kuantan. Histological results showed the presence of mature oocytes from a sample collected in April and May 2018, which indicate an extended gamete release pattern for these species within KCR. The gamete maturity coincided with the peak sea surface temperature within KCR from April until May. Both Acropora species spawned between 10-11 nights after the full moon. Present results also indicated that both Acropora species have optimal pelagic larvae duration (PLD) between 6 – 8 days after spawning. This study contributed to the limited knowledge of coral reproductive biology on the east coast of Peninsular Malaysia. In addition, the timing of coral spawning provides valuable data for population connectivity modelling.